DAMPAK IMPLEMENTASI KEBIJAKAN YAYASAN DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP EFEKTIVITAS PEMBELAJARAN - Mohamad Imron Rosyid (Pascasarjana Unviersitas Majalengka, 2019)
The research was motivated by the phenomenon of the low effectiveness of vocational learning. Not yet optimal implementation of foundation policies and school principal leadership are the dominant factors in increasing the effectiveness of vocational learning. The research aims to determine the impact of these two factors. The research method uses a survey with a quantitative approach, with the main data collection tool in the form of a questionnaire. The results showed that the results of the descriptive analysis of the implementation of the foundation's policies, the principal's leadership, and the effectiveness of learning were in good condition, although there were still weak aspects. From the results of the verification analysis, the implementation of the foundation's policies and the leadership of the school principal had a significant impact on the effectiveness of learning, both partially and collectively. In conclusion, the implementation of the foundation's policies and the leadership of the school head had a significant impact on the effectiveness of vocational learning.